2021
DOI: 10.1186/s13287-021-02527-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic summary of survival and death signalling during the life of hair follicle stem cells

Abstract: Hair follicle stem cells (HFSCs) are among the most widely available resources and most frequently approved model systems used for studying adult stem cells. HFSCs are particularly useful because of their self-renewal and differentiation properties. Additionally, the cyclic growth of hair follicles is driven by HFSCs. There are high expectations for the use of HFSCs as favourable systems for studying the molecular mechanisms that contribute to HFSC identification and can be applied to hair loss therapy, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 278 publications
(309 reference statements)
0
51
0
Order By: Relevance
“…For a more detailed characterization, we subclustered SEB yielding five distinct SEB subpopulations in skin SGs and three in PGs ( Figure 2 A). Closer characterization of the subpopulations present in the skin showed high expression levels of the hair follicle (HF)-associated genes, such as Krt27 , Krt17 , Hoxc13 and Wnt5a in the major three subpopulations (HF/SEB1, HF/SEB2, HF/SEB3) ( Supplementary Figure S2 ) [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. The two main clusters in PG were identified as early SEB and late SEB and were both also found in the skin, though at significantly smaller numbers.…”
Section: Resultsmentioning
confidence: 99%
“…For a more detailed characterization, we subclustered SEB yielding five distinct SEB subpopulations in skin SGs and three in PGs ( Figure 2 A). Closer characterization of the subpopulations present in the skin showed high expression levels of the hair follicle (HF)-associated genes, such as Krt27 , Krt17 , Hoxc13 and Wnt5a in the major three subpopulations (HF/SEB1, HF/SEB2, HF/SEB3) ( Supplementary Figure S2 ) [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. The two main clusters in PG were identified as early SEB and late SEB and were both also found in the skin, though at significantly smaller numbers.…”
Section: Resultsmentioning
confidence: 99%
“…During the hair cycle, the hair matrix expresses Wnt3a and Wnt10b, and DP responds to Wnt pathway signals to activate HF epithelial cells ( 3 , 20 , 22 ). Matrix proliferation requires epithelial Wnt/β-catenin; inhibiting β-catenin or exogenously adding Dickkopf (Dkk) can inhibit matrix growth and anagen processing ( 23 ).…”
Section: Emi In Hf Morphogenesis and Cyclic Regenerationmentioning
confidence: 99%
“…Simultaneously, Wnt signaling controls the activity of hair sheath-specific signals, showing its function in HFSC-specific differentiation ( 24 , 25 ). Furthermore, epithelial Wnt signaling is involved in DP-inducible properties, and experiments found that the addition of Wnt3a rebuilt the inducibility of DP that has been lost in vitro in both mice and human tissues ( 22 , 26 ).…”
Section: Emi In Hf Morphogenesis and Cyclic Regenerationmentioning
confidence: 99%
“…For a more detailed characterization, we subclustered SEB yielding five distinct SEB subpopulations in skin SGs and three in PGs (Figure 2A). Closer characterization of the subpopulations present in the skin showed high expression levels of hair follicle (HF)-associated genes, such as Krt27, Krt17, Hoxc13 and Wnt5a in the major three subpopulations (HF/SEB1, HF/SEB2, HF/SEB3) (Supplementary Figure 2) [55]- [61]. The two main clusters in PG were identified as early SEB and late SEB, and were both also found in the skin, though at significantly smaller numbers.…”
Section: Significant Differences In Gene Expression Between Sebocytes Derived From Skin Sgs and Pgsmentioning
confidence: 99%